Risk and protective factors for falls on stairs in young children: multicentre case–control study - Kendrick, Denise; Ablewhite, Joanne; Zou, Kun; Watson, Michael; Coupland, Carol; Kay, Bryony; Hawkins, Adrian; Reading, Richard (BMJ Group, 2016)
Aim: To investigate risk and protective factors for stair falls in children aged <5 years.